Perspectives on the application of 3D motion design in marketing - Permiakova, Irina; Escobar Rios, Andrea; Martínez Pantoja, Yadira Ixchel; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
The application of 3D motion design in marketing strategies offers a dynamic and immersive approach to engage audiences and enhance brand visibility. This abstract explores the various perspectives and benefits of integrating 3D motion design into marketing campaigns, including increased customer engagement, enhanced brand storytelling, and differentiation in a competitive landscape.
Vedoucí práce: Andrea Escobar Rios
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses